Management Of School Library And Work Motivation On Library Management Performance In Kec Buay Pemaca Okus District - Syuhada, Dahlia; Arafat, Yasir; Yan, Alhadi (Jurnal Pendidikan Tambusai, 2021)
This study aims to identify and analyze: (1) school library management; (2) work motivation, and (3) library manager performance. This research is a quantitative study using a survey method. This research was conducted in Buay Pemaca District OKUS Regency with 30 library managers as respondents. Data collection techniques used questionnaires and documentation. Validity test using the SPSS program. Meanwhile, the reliability test used Cronbach's Alpha. The prerequisite test analysis used simple regression and multiple regression techniques. The results showed that: (1) there is a positive and significant relationship between school library management and work motivation on the performance of library managers with a correlation value of 0.018 with a percentage of the relationship of 97.8% while 2.2% is determined by other factors not mentioned in this research